1985
DOI: 10.1007/bf00254477
|View full text |Cite
|
Sign up to set email alerts
|

Application of the parametric scan in the investigation of uteroplacental blood flow

Abstract: We developed a new radioisotope technique to measure placental blood flow for the early detection of placental insufficiency. Using the parametric scan, placental perfusion was measured in 80 late-pregnant women. The T-maximum pictures obtained made it possible to differentiate between the vascular and intervillous phases of placental blood flow. The time period of intervillous phase calculated as the percentage of the whole placental Tmax was given as the intervillous perfusion index (IPI). It was demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…There are no measurements of placental perfusion with which to compare these results. In an earlier study (3) radioisotope techniques were used to detect changes in utero-placental blood flow, in compromised pregnancy. The transit of the isotope across the placenta in the vascular and intervillous phases was extracted from the time-activity curve.…”
Section: Discussionmentioning
confidence: 99%
“…There are no measurements of placental perfusion with which to compare these results. In an earlier study (3) radioisotope techniques were used to detect changes in utero-placental blood flow, in compromised pregnancy. The transit of the isotope across the placenta in the vascular and intervillous phases was extracted from the time-activity curve.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Ftotal shows that the placental weight differ between IUGR and AGA but does not reflect placental functional parameters, which should be explained by F. Two authors evaluated placental perfusion in humans and found very similar F mean values. In an earlier study, Bodis et al [ 30 ] used isotope techniques to estimate placental perfusion and found F mean of 110 mL/min/100ml. Gowland et al [ 31 ] performed echo planar imaging at 0.5 T in 15 patients and found F mean of 176±24 mL/min/100ml.…”
Section: Discussionmentioning
confidence: 99%